[PP.24.01] SELECTIVE REDUCTION OF PRE-LOAD IMPROVES VENTRICULAR DIASTOLIC FUNCTION IN HYPERTENSION. (September 2017) - Faconti, L.; Farukh, B.; Brett, S.; Chowienczyk, P.
Abstract : Objective: Increased circulating blood volume may contribute to hypertension and could adversely affect ventricular diastolic function via an effect on cardiac pre-load. We examined a novel test of acute pre-load reduction on echocardiographic indices of diastolic function in patients with essential hypertension. Design and method: Patients with essential hypertension on treatment (n = 44, mean ± SD age 56 ± 12 years, blood pressure, BP, 141 ± 17/86 ± 13 mmHg) underwent trans-thoracic echocardiography (TTE) including assessment of inferior vena cava (IVC) diameter and superior vena cava (SVC) blood flow (Doppler flow velocity of S wave). Diastolic function was assessed through measurement of left atrial volume (LAV), peak mitral early (E) and late diastolic filling velocities (A) and their ratio (E/A), E wave deceleration time (DT) and the ratio (E/E') between E and tissue Doppler annular early diastolic velocity. TTE was repeated after passive leg raising (inducing a gravitational transfer of blood from the lower limbs toward the intrathoracic compartment) and supra-diastolic, sub-systolic pressure inflation of thigh cuffs (reducing the transfer of blood from lower limbs toward the intrathoracic compartment) in order to respectively increase and decrease cardiac pre-load. Results: Baseline BP and heart rate were not significantly altered by the interventions (mean change in systolic BP and heart rate < 2 mmHg and < 2 bpm respectively). Leg raising had minimal effects on IVC/SVC indices and no significant effects on indices of diastolic function. By contrast, leg cuffs significantly decreased IVC diameter (from 1.35 ± 0.43 to 1.10 ± 0.33 cm, and SVC S wave velocity from 65 ± 21 to 54 ± 18 cm/s, both p < 0.01) and improved all indices of diastolic function: LAV reduced from 49.1 ± 15.2 to 44.5 ± 13.6 ml, E/A from 1.09 ± 0.33 to 0.88 ± 0.34, E/E' from 8.16 ± 0.41 to 6.8 ± 2.3, DT increased from 205 ± 110 to 236 ± 49 all p < 0.01). Conclusions: Diastolic function in hypertension can be altered by a BP independent reduction of cardiac pre-load, induced non-invasively during a conventional TTE. The novel test of pre-load reduction proposed here might prove useful in identifying patients with elevated pre-load who would benefit from pharmacological treatment to reduce this.